2014
DOI: 10.1525/sp.2014.12241
|View full text |Cite
|
Sign up to set email alerts
|

Reproducing Stories: Strategic Narratives of Teen Pregnancy and Motherhood

Abstract: Pregnant and parenting young women are simultaneously silenced and overrepresented by raced and classed social narratives on adolescent childbearing in the United States. These narratives posit teen childbearing as an unequivocal social, health, and economic problem, although some scholars and policy makers construct alternative narratives that focus on inequalities and propose different perspectives on causes and consequences. Narrative inquiry that analyzes how stories are produced and utilized can enable a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…The topic of teen pregnancy commonly positions young parents as either redeemable good mothers or irresponsible, bad biocitizens (Greenhalgh & Carney, 2014), without considering whole lives and lived experiences (Barcelos & Gubrium, 2014). The value of a participatory methodology such as body mapping is that rather than being an object to be analysed and mined for data, the research participant becomes a co-creator of knowledge and information.…”
Section: Discussionmentioning
confidence: 99%
“…The topic of teen pregnancy commonly positions young parents as either redeemable good mothers or irresponsible, bad biocitizens (Greenhalgh & Carney, 2014), without considering whole lives and lived experiences (Barcelos & Gubrium, 2014). The value of a participatory methodology such as body mapping is that rather than being an object to be analysed and mined for data, the research participant becomes a co-creator of knowledge and information.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the dominant social narratives on adolescent childbearing in the United States are based on both race and class [22], and disparities in US teen birth rates are reported by ethnicity and socioeconomic status [59,61,62]. Data limitations here did not, however, permit an exploration of normative differences by demographic characteristics beyond age.…”
Section: Discussionmentioning
confidence: 99%
“…After consultation with other authors, the first author sought to develop related etic codes from extant conceptual frameworks in qualitative studies on normative contexts of early childbearing. Three such studies were identified [22,31,54], and 10 resulting etic codes on social norms were used in analysis. Subsequently, a second codebook on social norms was developed specifically for the analysis of comments and associated responses that were initially coded as “Value Statements or Judgement Surrounding Teen Pregnancy.” In the final phase of analysis, the first author checked the integrity of the themes in relation to their component coded extracts as well as to the dataset as a whole.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations